2017
DOI: 10.1038/s41598-017-03561-8
|View full text |Cite
|
Sign up to set email alerts
|

Autotransporter domain-dependent enzymatic analysis of a novel extremely thermostable carboxylesterase with high biodegradability towards pyrethroid pesticides

Abstract: The EstPS1 gene, which encodes a novel carboxylesterase of Pseudomonas synxantha PS1 isolated from oil well-produced water, was cloned and sequenced. EstPS1 has an open reading frame of 1923 bp and encodes the 640-amino acid carboxylesterase (EstPS1), which contains an autotransporter (AT) domain (357–640 amino acids). Homology analysis revealed that EstPS1 shared the highest identity (88%) with EstA from Pseudomonas fluorescens A506 (NCBI database) and belonged to the carboxylesterase family (EC 3.1.1.1). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…These findings suggest that the smaller Sp in CH from strain C5pp probably is assisted by the Tmd to allow successful anchoring and translocation of the polypeptide across the inner membrane. The Sp region has been reported to contribute toward activity and stability of esterases of the GDSL family (37). This was recently observed for carboxyl esterase (EstPS1), where the presence of Sp yielded a soluble and active enzyme, while EstPS1ΔSp protein was insoluble (37).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These findings suggest that the smaller Sp in CH from strain C5pp probably is assisted by the Tmd to allow successful anchoring and translocation of the polypeptide across the inner membrane. The Sp region has been reported to contribute toward activity and stability of esterases of the GDSL family (37). This was recently observed for carboxyl esterase (EstPS1), where the presence of Sp yielded a soluble and active enzyme, while EstPS1ΔSp protein was insoluble (37).…”
Section: Discussionmentioning
confidence: 84%
“…The Sp region has been reported to contribute toward activity and stability of esterases of the GDSL family (37). This was recently observed for carboxyl esterase (EstPS1), where the presence of Sp yielded a soluble and active enzyme, while EstPS1ΔSp protein was insoluble (37).…”
Section: Discussionmentioning
confidence: 84%
“…Taken together, a new pyrethroid decomposing enzyme has been identified and cloned in this study. The novelty of this newly identified protein is its lack of the conserved pentapeptide motif, Gly-X-Ser-X-Gly, and AT domain 29 , found in other pyrethroids degrading enzymes (Table S1 ). Utilizing fenpropathrin as asubstrate, we have demonstrated that this novel enzyme is thermostable and can tolerate a wide range pH conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few studies have been carried out on microbially produced degradative enzymes and genes. The key degradation enzymes (oxygenases, carboxylesterases, and aminopeptidases) in the microbial degradation of pyrethroids have been puri ed and characterized (Chen et al 2013;Cai et al 2017;Tang et al 2017). By isolating and characterizing these functional enzymes, detailed mechanisms of microbial degradation can be determined and pyrethroid-contaminated environments can be bioremediated (Hu et al 2019).…”
Section: Introductionmentioning
confidence: 99%